Law Enforcement against The Criminal Act of Sale of Cytotec Drugs at The Sukoharjo Resort Police Office - Yoga Subekti Nugroho; Marisa Kurnianingsih (Proceeding International Conference Restructuring and Transforming Law, 2025)
Law enforcement against the illegal sale of Cytotec drugs for abortion purposes without a distribution permit in Sukoharjo is a serious concern because its use is regulated and requires a doctor's prescription, so that its impact is dangerous to public health. Cytotec, which should be used to treat gastric ulcers, is often misused as an abortion drug. This study uses an empirical legal method by collecting primary data through interviews and secondary data from various legal literature. The results of the study show that the Sukoharjo Police Resort succeeded in uncovering the drug sales network through cyber patrols and covert transactions. However, law enforcement still faces various obstacles, such as the modus operandi of online sales that make it difficult to track the perpetrators and the lack of witnesses willing to provide information. In terms of regulation, the distribution of Cytotec without a permit is a criminal act that can be prosecuted under the Health Law. Misuse of this drug risks causing serious health complications, including severe bleeding and the risk of death. To overcome the problem of the illegal distribution of Cytotec (Misoprostol), the government and BPOM have made various concrete efforts, such as raids and blocking sites and social media accounts that sell this drug illegally. For example, BPOM routinely collaborates with the Ministry of Communication and Information (Kominfo) to close access to e-commerce and marketplaces that are suspected of selling drugs without a distribution permit.